Dual-Wavelengths Spectrophotometric Determination of Trace Amounts of Copper with Dibromo-o-Nitrophenylflurone - Gao, Hong-Wen; Xie, Rong; Zhang, Huai-Zhong; Zhang (Asian Journal of Chemistry, 2010)
The reaction between copper (Cu2+) and the chromogenic reagent, dibromo-o-nitrophenylflurone (DBNPF) was used for the determination of trace amounts of copper by primary-secondary wavelength spectrophotometry (PSWS). It was selective at pH 8 and selective in the presence of fluoride and triethanolamine. The new dual-wavelength spectrophotometry, PSWS, gave more precise and more accurate results than ordinary spectrophotometry because it can utilize simultaneously the peak absorption and the valley absorption of the reacted solution to decrease the influence of excess of ligand. By analyzing several samples, the relative standard deviations were less than 4.7% and the recovery rate of Cu between 92.5 and 107%.